Rethinking value in health innovation: from mystifications towards prescriptions. Issue 2 (3rd April 2019) - Mazzucato, Mariana; Roy, Victor
ABSTRACT: Debates over value in health innovation in the U.S. and Europe have become increasingly dominated by "value-based pricing". We examine this prevailing narrative and its weaknesses and then present an alternative framework for rethinking value in health. Drawing on scholarship from the political economy of innovation, we argue that value in health must be considered in terms of both value creation as a collective process amongst public and private actors, as well as value extraction that occurs due to financialization. In building this alternative framework, we pose three questions that present areas for further research and public policy change.